Retrofit of Natural Gas Turboexpansion Plants to Work in Dual Mode - Díaz, María Soledad (2001)
A MINLP optimization model has been developed to retrofit an ethane extraction plant to work in both ethane production mode and ethane rejection mode. The process model is solved within a sequential process simulator that embeds different natural gas plants designs. Based on an initial Basic Turboexpansion Process, the program determines the optimum process technology that maximizes either ethane or propane recovery and its associated operating conditions.